Pengaruh Pengungkapan Emisi Karbon, Kinerja Lingkungan dan Corporate Social Responsibility terhadap Nilai Perusahaan pada Perusahaan Pertambangan yang Terdaftar di Bursa Efek Indonesia Tahun 2020-2023 - Annisa Putri; Rana Fathinah Ananda; Hasbiana Dalimunthe; Fauziah Rahman (BADAN PENERBIT STIEPARI PRESS, 2025)
The objective of this study is to examine the effect of carbon emission disclosure, environmental performance, and corporate social responsibility on firm value, both partially and simultaneously. This research adopts a quantitative approach using an associative method. The population consists of 105 mining companies, with purposive sampling selecting 35 companies over a four-year period, resulting in a total of 140 samples from mining companies that meet predetermined criteria and are listed on the Indonesia Stock Exchange during the period 2020–2023. The type of data used is quantitative, sourced from secondary data. Data collection methods involve annual reports and sustainability reports published by mining companies listed on the Indonesia Stock Exchange from 2020 to 2023. The data analysis method employed is multiple linear regression analysis, using the SPSS (Statistical Program for Social Science) software, version 15. The partial test results show that carbon emission disclosure and corporate social responsibility do not have a significant effect on firm value in mining companies listed on the Indonesia Stock Exchange for the years 2020–2023. However, environmental performance partially has an influence on firm value for these companies. Simultaneously, the study demonstrates that carbon emission disclosure, environmental performance, and corporate social responsibility collectively have an effect on firm value in mining companies listed on the Indonesia Stock Exchange during the 2020–2023 period.